2019
DOI: 10.1177/1932296819841911
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Approach to Flash Glucose Monitoring: An Expert Recommendation

Abstract: The flash glucose monitoring (FGM) system FreeStyle Libre® is a device that measures interstitial glucose in a very simple way and indicates direction and speed of glucose change. This allows persons with diabetes to prevent hypoglycemic and hyperglycemic events. Scientific evidence indicates that the system can improve glycemic control and quality of life. To obtain the maximum benefit, it is necessary to properly handle glucose values and trends. Due to the generalization of the system use, the purpose of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 19 publications
0
20
0
6
Order By: Relevance
“…Glycemic control and reduction of hyperglycemia or hypoglycemia events are the main challenges in the clinical experience to achieve decreases of blood glucose variability ( 248 ). Indeed, levels of glucose and its constant fluctuations are good indicators of organ dysfunctions such as those associated with infections ( 249 ).…”
Section: Methods and Inclusion Criteriamentioning
confidence: 99%
“…Glycemic control and reduction of hyperglycemia or hypoglycemia events are the main challenges in the clinical experience to achieve decreases of blood glucose variability ( 248 ). Indeed, levels of glucose and its constant fluctuations are good indicators of organ dysfunctions such as those associated with infections ( 249 ).…”
Section: Methods and Inclusion Criteriamentioning
confidence: 99%
“…Compared with SMBG, CGM with interstitial glucose measurements at 5 min intervals provides a more comprehensive record during the day and night periods [ 20 , 34 ]. In recent years, Chico et al reported that flash glucose monitoring, a new approach to glucose monitoring, had a long sensor lifetime of 14 days and emerged as a practical solution to the glucose monitoring [ 36 ].…”
Section: Metrics and Measurement Of Gvmentioning
confidence: 99%
“…Long-term GV CV Variation around the mean blood glucose of HbA1c, FPG and PPG between sequential visits [19] SD Magnitude of variability relative to mean blood glucose of HbA1c, FPG and PPG between sequential visits [19] VIM Based on logarithmic curve fitting (the natural logarithm of SD over the natural logarithm of the mean) [22] Short-term GV Within-day or between-day GV CV Variation around the mean blood glucose [18] SD Magnitude of variability relative to mean blood glucose [18] LBGI/HBGI Measure of frequency and magnitude of hypoglycemia or hyperglycemia [31] ADRR Sum of the daily peak risks for hypoglycemia and hyperglycemia [32] Within-day GV MAGE Mean differences from peaks to nadirs [23] MAG Absolute differences between sequential readings divided by the time [8] CONGA Difference between a current blood glucose reading and a reading taken hours earlier [25] TIR Percentage of time spent within the target glucose range of 3.9-10.0 mmol/L during a 24-h period [26,27] Between-day GV MODD Absolute differences between two glucose values measured at the same time with a 24 h interval [28] AGP/IQRs Distribution of glucose data at a given timepoint [29,30] Measuring method of GV SMBG Reflected blood glucose fluctuations on the timescale of hours or days [20] CGM Interstitial glucose measurements at 5 min intervals [20,34] Flash glucose monitoring Measured interstitial glucose and indicated direction and speed of glucose change [36] Within-day GV Similar to long-term GV, SD and CV are also the common metrics of short-term GV. When averaging daily SD or CV, the mean of within-day daily GV can also be estimated over the stated time [18].…”
Section: Various Metrics and Measure Of Gv Description Or Definition mentioning
confidence: 99%
“…20 Flash glucose monitoring, a new approach to glucose monitoring, has emerged as a practical solution to the previous challenges of glucose monitoring. 21 In particular, the FreeStyle Libre flash glucose monitor (Abbott Diabetes Care, Witney, UK) enables patients to conveniently access their glucose levels at any time by scanning a sensor for glucose readings. The device does not require calibration, has a long sensor lifetime of 14 days, and is relatively affordable.…”
Section: Introductionmentioning
confidence: 99%